Pemeliharaan Pada Ruas Jalan Tri Darma Suak Bujang Kota Palembang - adli sukma, Farid Adli Sukma; Farlin Rosyad (Yayasan Literasi Sains Indonesia, 2025)
Road maintenance is an important part of maintaining the quality and safety of transportation infrastructure. This report discusses maintenance activities carried out on the Tri Darma Suak Bujang Road section as an effort to improve the comfort and safety of road users and extend the service life of the road. The methods used in maintenance activities include road condition surveys, identification of damage such as cracks, holes, and surface deformation, and implementation of repair actions according to the level of damage. The results of these activities show a significant improvement in road conditions after routine and periodic maintenance. With the right and sustainable maintenance program, it is expected to minimize further damage and support smooth transportation in the Suak Bujang area